2021
DOI: 10.20473/fmi.v56i4.24602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Celery Extract on Fructose Induced Insulin Resistance Rattus norvegicus

Abstract: Diabetes mellitus (DM) is one of the global health problems and in the top 4th ranks as the main cause of death in developing countries (IDF, 2015). The pathogenesis of type II DM involves abnormalities in insulin secretion and activity that leads to insulin resistance. This research aims to study the efficacy of celery (Apiumgraveolens) as a prevention of insulin resistance. In this study, the samples were 45 Wistar rats (Rattus norvegicus), male sex, aged 4-6 weeks, weight 150-175 grams,and had normal fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The HOMA-IR value is used to determine IR. The HOMA-IR values were categorized as follows: ≤2.60, normal; 2.60-3.80, borderline; and >3.80, a high correlation with IR [29][30][31].…”
Section: Homa-ir Valuementioning
confidence: 99%
“…The HOMA-IR value is used to determine IR. The HOMA-IR values were categorized as follows: ≤2.60, normal; 2.60-3.80, borderline; and >3.80, a high correlation with IR [29][30][31].…”
Section: Homa-ir Valuementioning
confidence: 99%
“…1,2 The primary problems associated with DM are high blood glucose levels due to a shortcoming in insulin production from pancreatic β cells and insulin resistance activity in peripheral tissues. 3,4 Persistent hyperglycemia increases the formation of free radicals that cause oxidative stress. 5,6 Several studies reported that the oxidant-antioxidant status of the diabetic rat model can be observed by the increased malondialdehyde (MDA) levels.…”
Section: Introductionmentioning
confidence: 99%